Sosialisasi Penanaman Nilai Agama Terhadap Perilaku Remaja Di Desa Toloti’o Kecamatan Bone Pantai Kabupaten Bone Bolango - Djafar, Lucyane (Universitas Pahlawan Tuanku Tambusai, 2023)
This dedication aims to implement a strategy of instilling religious values through Al-Quran reading activities through the stages, namely the planning stage, the implementation stage. At the planning stage, training activities are held. After examining the role of the environment in instilling religious moral values in adolescents, it can be concluded that the Toloti Village environment in carrying out the role of instilling religious values in its youth can be said to work with the contribution of youth who realize the results of their religious learning from what has been instilled by their environment. They can realize it in their daily lives. Like a teenager who has made congregational prayers at the prayer room a mandatory daily routine and has become a good habit for him. Keywords: Inculcation of Religious Values, Youth of Toloti’o Village